Improving walking in persons after trans-femoral amputation by means of electrical stimulation - Burger, Helena (Rehabilitacija (Ljubljana), 2014)
Background: A precondition for walking after trans-femoral amputation is successful control of the above-knee prosthesis for which the person needs strong muscles of the stump. The goal of the present study was to determine whether electrical stimulation of the great gluteal muscle on the amputated side improves the control of an unlocked prosthetic knee and walking of persons after trans-femoral amputation. Methods: Thirty-two men after trans-femoral amputation who came to their first rehabilitation session and had never walked with a prosthesis before were randomly divided into two groups of 16 persons: a group that received electrical stimulation (ES group) and a control group. Before discharge the ability to control unlocked prosthetic knees, walking distance, need for crutches and ability to climb stairs were evaluated. Results: There was no difference between the two groups in age, cause of amputation, condition of the stump, walking distance, climbing of stairs and need for crutches at admission. Six persons who received ES and three from the control group were able to control the unlocked prosthetic knee and therefore received one. The persons from the ES group walked significantly longer before discharge and had less need for crutches while walking than persons from the control group. Conclusions: Electrical stimulation of the great gluteal muscle improves control of an unlocked prosthetic knee and walking of persons after trans-femoral amputation.
Keywords: Amputation; Electric Stimulation; električna stimulacija; Gait; hoja; nadkolenska amputacija; rehabilitacija; Rehabilitation; trans-femoral amputation; vocational rehabilitation